2004
DOI: 10.2514/1.9562
|View full text |Cite
|
Sign up to set email alerts
|

Radio-Frequency Oxygen Plasma as a Sterilization Source

Abstract: An oxygen plasma sustained at 13.56 MHz in a standardized reactor with a planar induction coil was used for biological decontamination experiments. Optical emission, mass spectrometry, Langmuir probe, and electrical measurements were applied to detection of chemical species and ion-energy and flux analysis. These diagnostics identified a plasma-mode transition in the range of 13-67-Pa pressure and 100-330-W power to the induction coil. At higher pressure and lower power, the plasma was sustained in a dim mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 55 publications
1
50
0
Order By: Relevance
“…Effectiveness of oxygen plasma in the sterilization processes is confirmed experimentally by Bol'shakov et al (1) , and it is shown that metastable molecules O * 2 ( 1 ∆ g ) and atomic oxygen O play an important role in microbial inactivation. These radicals prompt chemical alteration and volatilization of biological matters.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Effectiveness of oxygen plasma in the sterilization processes is confirmed experimentally by Bol'shakov et al (1) , and it is shown that metastable molecules O * 2 ( 1 ∆ g ) and atomic oxygen O play an important role in microbial inactivation. These radicals prompt chemical alteration and volatilization of biological matters.…”
Section: Introductionmentioning
confidence: 62%
“…It can be said from the results obtained above that there is a high possibility to produce the optimal design by the numerical analysis because of the existence of maximal value of OPE. The focus of high density area of O 3 on the dielectric surface is the key technology of the sterilization in bioprocess (1) , and the optimal design of the sterilizer from the viewpoint of energy efficiency can be made by numerical simulation developed here, where the energy efficiency must be the practical knowledge.…”
mentioning
confidence: 99%
“…Taking into account the high efficiency of oxygen-based plasmas, literature on low pressure sterilization has mainly focused on these kind of plasmas, nevertheless, inert gas plasmas are in some cases still employed for bacterial inactivation (Liu&Chen, 2008. Recently, many studies (Bol'shakov et al, 2004, Boscariol et al, 2008, Cvelbar et al, 2006, Nagatsu et al, 2003, Rossi et al, 2008, Singh et al, 2009, Vicoveanu et al, 2008 on the effects of pure oxygen vacuum plasmas on bacteria have been conducted. Bol'shakov et al (Bol'shakov et al, 2004) published an interesting paper on the use of an oxygen RF plasma for sterilization purposes.…”
Section: Vacuum Plasmasmentioning
confidence: 99%
“…Recently, many studies (Bol'shakov et al, 2004, Boscariol et al, 2008, Cvelbar et al, 2006, Nagatsu et al, 2003, Rossi et al, 2008, Singh et al, 2009, Vicoveanu et al, 2008 on the effects of pure oxygen vacuum plasmas on bacteria have been conducted. Bol'shakov et al (Bol'shakov et al, 2004) published an interesting paper on the use of an oxygen RF plasma for sterilization purposes. The study was carried out for two operational modes: the inductively coupled mode and the capacitively coupled mode and it was found that the inductive mode offers a better efficiency in destroying bacterial cells.…”
Section: Vacuum Plasmasmentioning
confidence: 99%
“…In this case, the plasma has about one order of magnitude higher electron density and much stronger light emission, which both change abruptly at the transition power. [6][7][8][9][10][11][12][13][14] The E-H transition was a focus of both theoretical 7 and experimental 11-14 studies related to Ar, N 2, Ar/N 2 , O 2 , Ar/O 2 , H 2 , and Ar/H 2 plasmas used mainly for etching required, e.g., in semiconductor processing or in biological decontamination. Nevertheless, it has received little attention in the plasma polymer field.…”
mentioning
confidence: 99%